Flexographic Printing of Trametes versicolor Laccase for Indicator Applications. (1st April 2014) - Virtanen, Heini; Vehmas, Kaisa; Erho, Tomi; Smolander, Maria
<x xml:space="preserve">Abstract</x> Trametes versicolor laccase papers were prepared, and their suitability was tested for anticounterfeiting and oxygen indicator concepts in packaging applications. Laccase was coated and printed onto paper with a flexographic ink base, a sulfo polyester resin, Hydro‐Rez 1100D (HZ1100D). Laccase remains active on paper with flexographic ink HZ1100D after printing with flexographic press. Colour change of papers was observed when 2, 2‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) diammonium salt (ABTS) solution was applied to the paper. A strong colour change to dark green was obtained on the papers prepared by coating or printing of laccase with HZ1100D onto EUCA paper. EUCA paper appeared to be well suited for laccase‐based indicator applications because it remained rough even after ink deposition, allowing rapid absorption of ABTS solution. Finally, the indicators demonstrated to work as oxygen indicators in a package. Indicator colour was changed when oxygen was leaked to the package. As a conclusion, the laccase papers described here would be well suited for various indicator applications and could be produced using flexographic printing, allowing large scale manufacturing. Copyright © 2014 John Wiley & Sons, Ltd.